An articulated ankle–foot orthosis with adjustable plantarflexion resistance, dorsiflexion resistance and alignment: A pilot study on mechanical properties and effects on stroke hemiparetic gait. (June 2017) - Kobayashi, Toshiki; Orendurff, Michael S.; Hunt, Grace; Lincoln, Lucas S.; Gao, Fan; LeCursi, Nicholas; Foreman, K. Bo
Highlights: An articulated ankle–foot orthosis (AFO) with adjustable mechanical properties was presented. The AFO was tested in an individual post-stroke during gait. Change of the properties affected kinematics and kinetics of ankle and knee joints. Importance of measuring kinematics and kinetics to tune the AFO was suggested. Abstract: Mechanical properties of an articulated ankle–foot orthosis (AFO) are closely related to gait performance in individuals post-stroke. This paper presents a pilot study on the mechanical properties of a novel articulated AFO with adjustable plantarflexion resistance, dorsiflexion resistance and alignment, and its effect on ankle and knee joint kinematics and kinetics in an individual post-stroke during gait. The mechanical properties of the AFO were quantified. Gait analysis was performed using a 3D motion capture system with a split-belt instrumented treadmill under 12 different settings of the mechanical properties of the AFO [i.e. 4 plantarflexion resistances (P1 < P4), 4 dorsiflexion resistances (D1 < D4), 4 initial alignments (A1 < A4)]. The AFO demonstrated systematic changes in moment–angle relationship in response to changes in AFO joint settings. The gait analysis demonstrated that the ankle and knee angle and moment were responsive to changes in the AFO joint settings. Mean ankle angle at initial contact changed from −0.86° (P1) to 0.91° (P4) and from −1.48° (A1) to 4.45° (A4), while mean peak dorsiflexion angle changed from 12.01° (D1) to 6.40° (D4) at mid-stance. The novel articulated AFO appeared effective in influencing lower-limb joint kinematics and kinetics of gait in the individual post-stroke.